Saturation Height Modelling for Tight Sandstone Reservoirs with Gas Diffusion Dynamics Taken into Account - Zhou Lyu; Zhilun Yang; Yuhong Hao; Shunzhi Yang; Liqiong Wang; Sen Chang; Xiaomin Xue; Jing Li (Geofluids)
Interpreting and predicting the saturation of tight sandstone gas reservoirs are the key task to improve the reservoir development. The role of gas diffusion dynamics is stronger than that of buoyancy during the gas accumulation of tight sandstone reservoirs. In this study, a saturation height model that takes gas diffusion dynamics into account is proposed, which can complement logging saturation interpretation and provide a better practice in saturation prediction. Taking the study of the Sulige tight sandstone gas reservoir in China as an example, the saturation height model compares the controlling factors and uncertainties affecting the saturation distribution, characterizes the complex gas-water distribution, and determines the lower gas charging limits. This study concludes that the configuration between gas diffusion dynamics and reservoir capillary pressure controls the distribution of saturation. The buoyancy effect only serves to improve the saturation at regional uplifts with good petrophysical properties. The different saturation characteristics in the central, western, and eastern parts of the Sulige gas field are precisely caused by the different configurations of source rock quality and reservoir quality. This study provides a key reference for static model and development deployment.